DIDACTIC INNOVATIONS IN GEOMETRY TO PROMOTE THE INCLUSION OF STUDENTS WITH MILD COGNITIVE DISABILITY - Diana Patricia Berna; Rodrigo Ricardo Paredes (DIALÉCTICA, 2026)
This scientific essay examined, from an interpretive documentary review, how different teaching innovations in school geometry can promote the inclusion of students with mild cognitive disabilities without reducing it to mere presence or participation. The discussion started from a central idea: technology can open doors to curricular access, but it does not guarantee cognitive access on its own; inclusion is decided, above all, by the quality of the tasks and the mediations that guide geometric understanding and reasoning. The analysis was based on a corpus of 13 references published between 2021 and 2025, selected for their thematic relevance and editorial traceability, and organized around reading axes that connect teaching, accessibility, and meaningful learning. The development articulated principles of Universal Design for Learning (UDL) with the concrete-representational-abstract (CRA) progression to specify how experiences can be designed that support the construction of geometric relationships, justification, and transfer, avoiding illusions of inclusion where the student interacts but does not understand. As a contribution, the essay proposes didactic criteria for integrating technological resources and cognitive accessibility strategies into geometry sequences, specifying the pedagogical function of each mediation and guiding teaching decisions toward real, situated, and assessable inclusion in the classroom.